From learners to entrepreneurs: a study on inclination of university students towards entrepreneurship as a career option and the role of education - Naila Aaijaz; Mohamed Dahlan Ibrahim; Ghazali Ahmad (2012)
This study investigates the inclination of University Malaysia Kelantan (UMK) students towards entrepreneurship. Specifically it aims to examine the relationship between entrepreneurship education and university students’ inclination towards entrepreneurship. This study also examines the moderating effects of demographic characteristics and family business background on budding entrepreneurs undergoing entrepreneurship education. The sampling population comprised of 84 students from the final year UMK students pursuing the undergraduate programme in Entrepreneurship. A self administered questionnaire was used in this study to collect data. The questionnaire consisted of 2 parts: the first part dealt with the Demographic characteristics of the respondents with sub-headings – personal information, family information, education and Willingness to become an entrepreneur. The second part was sub-divided into 2 parts – part A and B, whereby ‘Part A’ covered questions on personality traits (innate talents) of the respondents and ‘Part B’ comprised of questions on experiential or acquired traits. That is knowledge and skills acquired due to socioeconomic forces. The role of Role models in form educators, books and technology in promoting entrepreneurship was also discussed. After screening a total of 80 questionnaires were deemed completed and usable. This yielded a response rate of 95.2 percent. Descriptive analysis, factor analysis, multiple regression, one-way ANOVA, independent sample t-test were used to test the hypothesized proposition. The results of factor analysis suggested that university students’ entrepreneurial inclination was due to their opting to pursue entrepreneurial study programme. Multiple regression was performed to examine the relationship between entrpreneurship education and inclination towards entrepreneurship. The results showed that the role of university in promoting entrepreneurship have statistically significant relationship with student inclination towards entrepreneurship. The hypothesis testing results indicated that in demographic characteristics fathers’ occupation and role of university did have an impact on university students’ inclination towards entrepreneurship.